Effect of Kinesio Taping on Pain Reduction in Carpal Tunnel Syndrome Patients: Meta-Analysis - Lely Tri Pangesti; Mehdya Vikia Murti (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Carpal Tunel Syndrome (CTS) is the most common nerve compression. Some cases of CTS have chronic symptoms. The most common complaint is